Causation of variables of aggressiveness with the features of temperament - A B Kruchkova (RUDN Journal of Psychology and Pedagogics, 2010)
The research paper analyses the results of intercommunication of characteristics of temperament and aggressiveness of 10-11 class pupils in Moscow general schools.